1999
DOI: 10.1152/ajpheart.1999.276.4.h1323
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ischemic preconditioning is mediated by opening of ATP-sensitive potassium channels in the rabbit heart

Abstract: Cardioprotection from preconditioning reappears 24 h after the initial stimulus. This phenomenon is called the second window of protection (SWOP). We hypothesized that opening of the ATP-sensitive potassium (KATP) channel mediates the protective effect of SWOP. Rabbits were preconditioned (PC) with four cycles of 5-min regional ischemia each followed by 10 min of reperfusion. Twenty-four hours later, the animals were subjected to sustained ischemia for 30 min followed by 180 min of reperfusion (I/R). Glibencla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 38 publications
6
47
0
2
Order By: Relevance
“…8,26b This is because the acquisition of cardiac resistance to ischemia after ischemic preconditioning or heat shock is a multifactorial phenomenon that includes several other possible mechanisms besides the induction of Ն1 members of the heat-shock protein family. These include the activation of protein kinase C, 27,28 receptor tyrosine kinase, 29 stressactivated MAPKAP kinase 2, 30 nuclear factor-B, 31 nitric oxide synthase(s), 32,33 antioxidant defense systems such as increased activities of SOD 34 and catalase, 35 opening of ATP-sensitive potassium channels, 15,36 or possibly other unknown mechanisms. Some of the above mediators may have a role in signaling pathways leading to the synthesis of Ն1 of the protective proteins, including HSP 70.…”
Section: Okubo Et Al Gene Transfer Of Heat-shock Protein 70 879mentioning
confidence: 99%
“…8,26b This is because the acquisition of cardiac resistance to ischemia after ischemic preconditioning or heat shock is a multifactorial phenomenon that includes several other possible mechanisms besides the induction of Ն1 members of the heat-shock protein family. These include the activation of protein kinase C, 27,28 receptor tyrosine kinase, 29 stressactivated MAPKAP kinase 2, 30 nuclear factor-B, 31 nitric oxide synthase(s), 32,33 antioxidant defense systems such as increased activities of SOD 34 and catalase, 35 opening of ATP-sensitive potassium channels, 15,36 or possibly other unknown mechanisms. Some of the above mediators may have a role in signaling pathways leading to the synthesis of Ն1 of the protective proteins, including HSP 70.…”
Section: Okubo Et Al Gene Transfer Of Heat-shock Protein 70 879mentioning
confidence: 99%
“…IPC exists in all species examined, including humans. 2 Mitochondrial K ATP (mitoK ATP ) channels feature prominently in the mechanism of cardioprotection [3][4][5][6][7][8][9] ; however, their precise role remains controversial. A decrease in the extent of mitochondrial Ca 2ϩ overload during ischemia and reperfusion (I/R) has been proposed to prevent or delay cell death, 10,11 and activation of the mitochondrial permeability transition (MPT) may be involved in this process.…”
mentioning
confidence: 99%
“…Downstream events include phosphorylation of STAT1/3 and activation of STAT dependent genes which include the COX-2 gene. Other events that mediate late preconditioning include NO release (through a PKG dependent mechanisms and opening of mitochondrial K(ATP) channels (Bernardo et al, 1999;Ockaili et al, 1999). It has been reported that the NO that mediates late preconditioning is derived from inducible NOS (iNOS).…”
Section: Sulindac Causes Cardiac Protection By Ischemic Preconditioningmentioning
confidence: 99%